Associations Between Retail Food Environment and Nutritional Quality of Food Purchases in French Households: The Mont'Panier Cross-Sectional Study. (14th June 2022) - Recchia, Daisy; Rollet, Pascaline; Perignon, Marlène; Vonthron, Simon; Tharrey, Marion; Darmon, Nicole; Feuillet, Thierry; Méjean, Caroline
Abstract: Objectives: The purpose of this study was to assess whether the retail food environment, measured by multiple indicators around home and in activity space, was associated with nutritional quality of food purchases. Methods: This cross-sectional study included 462 households from a quota sampling survey conducted in the south of France (Montpellier Metropolitan Area). The revised Healthy Purchase Index was implemented in order to assess nutritional quality of food purchases. Food environment indicators (presence, number, relative density and proximity of food outlets) were calculated around home and in activity space (around home, work, other places of activity and along commuting journeys) using a geographical information system. Six different types of food outlets were studied: supermarkets, markets, greengrocers, bakeries, other specialized food stores (butcher's, fishmonger's and dairy stores) and small grocery stores. Associations between food environment and nutritional quality of food purchases were assessed using multilevel models, and geographically weighted regressions to account for spatial non-stationarity. Models were adjusted for households' socioeconomic and demographic characteristics. Results: Nutritional quality of food purchases was positively associated with the number of greengrocers around home (1 vs 0: β = 0.25, 95%CI = [0.01, 0.49]; >1 vs 0: β = 0.25, 95%CI = [0.00, 0.50]), but negatively associated with the number of markets around home (1 vs 0: β = −0.20, 95%CI = [−0.40, 0.00]; >1 vs 0: β = −0.37, 95%CI = [−0.69, −0.06]). These associations varied across space in the studied area. For households with lower income, number of greengrocers in activity space was positively associated with nutritional quality of food purchases (1 vs 0: β = 0.70, 95%CI = [0.12, 1.3]; >1 vs 0: β = 0.67, 95%CI = [0.22, 1.1]). Conclusions: Greengrocers might be an efficient food store type to promote healthier dietary behaviors. Further studies, particularly interventional studies, are needed to confirm these results in order to guide public health policies in actions designed to improve the food environment. Funding Sources: Région Occitanie; Institut national de recherche pour l'agriculture, l'alimentation et l'environnement (INRAE); ANR (the French National Research Agency).